TP53 Gain-of-Function and Non–Gain-of-Function Mutations Are Associated With Differential Prognosis in Advanced Pancreatic Ductal Adenocarcinoma - Minggui Pan; Chen Jiang; Zheyang Zhang; Ninah Achacoso; Stacey E. Alexeeff; Aleyda V. Solorzano; Pam Tse; Elaine Chung; Tilak Sundaresan; Jennifer M. Suga; Sachdev Thomas; Laurel A. Habel (2023)
PURPOSE To examine the impact of TP53 gain-of-function (GOF) and non-GOF mutations on prognosis of advanced pancreatic ductal adenocarcinoma (PDAC) among patients with KRAS, CDKN2A, and SMAD4 comutations. METHODS This cohort included patients with locally advanced, recurrent, and de novo metastatic PDAC with next-generation sequencing performed from November 2017 to May 2022. We defined R175H, R248W, R248Q, R249S, R273H, R273L, and R282W as GOF and all other p53 mutations (mutp53) as non-GOF. We used Cox regression modeling to examine the association between GOF and non-GOF mutp53 and overall survival (OS), adjusting for demographics, performance status, Charlson comorbidity index, receipt of chemotherapy, and KRAS, CDKN2A, and SMAD4 comutations. RESULTS Of 893 total eligible patients, 68.5% had tumors with mutp53, 90.1% had KRAS mutations (mutKRAS), 44.7% had CDKN2A mutations (mutCDKN2A), and 17.0% had SMAD4 mutations. Among patients with mutp53, 121 had GOF and 491 had non-GOF. GOF mutp53 was associated with worse OS than non-GOF mutp53 (hazard ratio [HR], 1.27; 95% CI, 1.02 to 1.59) and wild-type p53 (wtp53; HR, 1.24; 95% CI, 0.98 to 1.57), whereas non-GOF was not associated with worse OS than wtp53 (HR, 0.95; 95% CI, 0.80 to 1.13). In addition, mutKRAS was associated with worse OS than wild-type KRAS in patients with mutCDKN2A (HR, 1.57; 95% CI, 0.88 to 2.80) but not in patients with wild-type CDKN2A (HR, 1.03; 95% CI, 0.76 to 1.39). CONCLUSION GOF and non-GOF mutp53 were associated with differential prognosis in advanced PDAC. The adverse effect of mutKRAS on OS appeared to be primarily driven by patients with mutCDKN2A. Our results provide new insight that could be helpful for prognostic stratification in clinical practice and for aiding future clinical trial designs.